Immunocapture isotope dilution mass spectrometry in response to a pandemic influenza threat. Issue 37 (5th September 2017) - Pierce, Carrie L.; Williams, Tracie L.; Santana, Wanda I.; Levine, Marnie; Chen, Li-Mei; Cooper, Hans C.; Solano, Maria I.; Woolfitt, Adrian R.; Marasco, Wayne A.; Fang, He; Donis, Ruben O.; Barr, John R.
Highlights: Immunocapture isotope dilution mass spectrometry (IC-IDMS) for influenza vaccines. IC-IDMS response to pandemic influenza threat A/Shanghai/2/2013 A(H7N9). MS's role in improved quality and time required for pandemic vaccine delivery. Abstract: As a result of recent advances in mass spectrometry-based protein quantitation methods, these techniques are now poised to play a critical role in rapid formulation of pandemic influenza vaccines. Analytical techniques that have been developed and validated on seasonal influenza strains can be used to increase the quality and decrease the time required to deliver protective pandemic vaccines to the global population. The emergence of a potentially pandemic avian influenza A (H7N9) virus in March of 2013, prompted the US public health authorities and the vaccine industry to initiate production of a pre-pandemic vaccine for preparedness purposes. To this end, we evaluated the feasibility of using immunocapture isotope dilution mass spectrometry (IC-IDMS) to evaluate the suitability of the underlying monoclonal and polyclonal antibodies (mAbs and pAbs) for their capacity to isolate the H7 hemagglutinin (HA) in this new vaccine for quantification by IDMS. A broad range of H7 capture efficiencies was observed among mAbs tested by IC-IDMS with FR-545, 46/6, and G3 A533 exhibiting the highest cross-reactivity capabilities to H7 of A/Shanghai/2/2013. MAb FR-545 was selected for continued assessment, evaluated by IC-IDMS for mAb reactivity against H7 in the H7N9 candidate vaccine virus and compared with/to reactivity to the reference polyclonal antiserum in allantoic fluid, purified whole virus, lyophilized whole virus and final detergent-split monovalent vaccine preparations for vaccine development. IC-IDMS assessment of FR-545 alongside IC-IDMS using the reference polyclonal antiserum to A/Shanghai/2/2013 and with the regulatory SRID method showed strong correlation and mAb IC-IDMS could have played an important role in the event a potential surrogate potency test was required to be rapidly implemented.